2007
DOI: 10.1002/dneu.20530
|View full text |Cite
|
Sign up to set email alerts
|

Androgen modulates the kinetics of the delayed rectifying K+ current in the electric organ of a weakly electric fish

Abstract: Weakly electric fish such as Sternopygus macrurus utilize a unique signal production system, the electric organ (EO), to navigate within their environment and to communicate with conspecifics. The electric organ discharge (EOD) generated by the Sternopygus electric organ is quasi-sinusoidal and sexually dimorphic; sexually mature males produce long duration EOD pulses at low frequencies, whereas mature females produce short duration EOD pulses at high frequencies. EOD frequency is set by a medullary pacemaker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Slower changes on the time scale of development and sexual maturation have been shown to be under the control of steroid hormones (Meyer et al, 1983;Meyer et al, 1987;Zakon et al, 1991;Dunlap and Zakon, 1998), affecting voltage-gated sodium and potassium channels in the electrocytes (Ferrari et al, 1995;McAnelly and Zakon, 2007). Given that the kinetics of sodium and potassium Zakon, 2007), it appears likely that the kinetics are matched for a given EOD frequency to minimize sodium waste current (Hasenstaub et al, 2010). Short-term reduction of EOD frequency, on the time scale of our experiments, may therefore provide little, if any, energy savings.…”
Section: Discussionmentioning
confidence: 99%
“…Slower changes on the time scale of development and sexual maturation have been shown to be under the control of steroid hormones (Meyer et al, 1983;Meyer et al, 1987;Zakon et al, 1991;Dunlap and Zakon, 1998), affecting voltage-gated sodium and potassium channels in the electrocytes (Ferrari et al, 1995;McAnelly and Zakon, 2007). Given that the kinetics of sodium and potassium Zakon, 2007), it appears likely that the kinetics are matched for a given EOD frequency to minimize sodium waste current (Hasenstaub et al, 2010). Short-term reduction of EOD frequency, on the time scale of our experiments, may therefore provide little, if any, energy savings.…”
Section: Discussionmentioning
confidence: 99%
“…Discovering how DHT amplifies the single-electrocyte discharge would provide valuable insights into the mechanisms by which steroid hormones regulate the intrinsic plasticity of excitable cells. Recent studies in a wave-type gymnotiform fish have shown that DHT acts over days to weeks to slow Na+ current inactivation (Ferrari et al, 1995) and delayed rectifying K+ current activation in electrocytes (McAnelly and Zakon, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…The EOD is a signal that is crucial for navigation, prey capture and species-specific communication in weakly electric teleost fishes which reflects the activity of single electrocytes (modified skeletal muscle-derived cells), as well as pacemaker neurons and their neuronal targets (107). The basis for the broadening of the waveform has been attributed to an AR-mediated slowing of the rate of inactivation of voltage-dependent sodium channels and concomitant slowing of voltage-dependent potassium channel activation (108, 109). Chronic AAS treatment has also been shown to alter the current densities and kinetics of potassium currents (101) and autonomic control of contractility (110) in cardiac muscle and intracellular calcium homeostasis and the voltage-dependence of potassium contractures in skeletal muscle (111, 112).…”
Section: Voltage-gated Ion Channelsmentioning
confidence: 99%